A72 Cyclists and traffic-related air pollution: comparison based on traffic density influence. Issue 2 (June 2015) - Van Oosten, Jean-Michel; Jacob, Luc; Int Panis, Luc; Dons, Evi; Bouland, Catherine
Abstract: Background: Several authors have stated that exposure of cyclists to traffic related air pollution decreases when distance from motorised traffic increases. In many cities, cyclists share the roads with cars, whereas in other urban situations, separate cycling infrastructures have been set up for cyclists. This study aims at determining if cycling on low density traffic roads decreases the individual exposure to traffic-related air pollution and its respiratory health consequences for cyclists in the Brussels-Capital Region. Methods: In March 2014, seventeen healthy regular cyclists rode two similar circular routes during morning rush hour. The "HIGH" route was mostly made of main roads, whereas the "LOW" route mainly of local roads. Real-time personal exposure to PM2.5 and black carbon were measured along the two routes. Respiratory symptoms were self-reported through completion of a questionnaire. Events occurrence during cycling (odour, coughing, discomfort) were localised on a map immediately after cycling. Objectivation of traffic-related events (traffic density, busses, odour or dust linked to road works) occurred through video recording of the trips. Results: Exposure of cyclists did not show significant difference between both routes for PM2.5, whereas it was the case for black carbon. Black carbon levels showed high spatio-temporal variability, reflecting the influence of local events. This was not the case for PM2.5 . Except for odours, the volunteers did not report any respiratory discomfort linked to exposure to air pollution during cycling. In order to compare the exposure of cyclists between both routes, an indicator of cumulative exposure to black carbon and PM2.5 was developed, taking into account mean values obtained from a reference monitoring station. The computed cumulative exposure indicator showed significant differences between the routes for both pollutants. Conclusions: Cycling on low traffic density roads in the Brussels-Capital Region seems to decrease the personal exposure of cyclists to black carbon, but not to PM2.5 . Exposure to traffic-related air pollution seems to be better reflected by car emission levels than monitored air quality.